2020
DOI: 10.17826/cumj.647253
|View full text |Cite
|
Sign up to set email alerts
|

Son trimester gebelerde doğum korkusunu etkileyen faktörler ve doğum korkusunun postpartum depresyon ve maternal bağlanma ile ilişkisi

Abstract: This study was conducted cross-sectionally to investigate factors effecting fear of delivery in last trimester pregnant women and its relationship with postpartum depression and maternal attachment. Materials and Methods: The study was conducted between the years 2014-2016 in a university hospital and in a state hospital maternity clinics in a western city. The study was made with 163 pregnant women. A questionnaire form which was created in accordance with literature that includes questions about sociodemogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
0
5
0
3
Order By: Relevance
“…The higher the variance ratio is, the stronger the factor structure of the scale is. The perceived self-efficacy and motivation sub-scale which consists of eleven items (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) assesses the pregnant woman's belief in spontaneous vaginal delivery. The perceived benefits sub-scale consisting of eight items (12)(13)(14)(15)(16)(17)(18)(19) assesses to what extent the pregnant woman is aware of the benefits of the spontaneous vaginal delivery in terms of her health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher the variance ratio is, the stronger the factor structure of the scale is. The perceived self-efficacy and motivation sub-scale which consists of eleven items (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) assesses the pregnant woman's belief in spontaneous vaginal delivery. The perceived benefits sub-scale consisting of eight items (12)(13)(14)(15)(16)(17)(18)(19) assesses to what extent the pregnant woman is aware of the benefits of the spontaneous vaginal delivery in terms of her health.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the mother's desire is one of the main factors that contribute to the increase in cesarean section rates (8). For this reason, it is important to determine the common underlying reasons behind women's wanting or preferring cesarean section without the presence of medical reasons (10). The Health Beliefs Model is one of the most frequently used concepts for determining health-related individual factors, leading to positive health behaviors, and planning health trainings (11).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that labor pain may increase due to the ambivalent feelings of pregnancy, the state of uncertainty, exaggerated birth scenes in the media, others' negative birth experiences, and concerns and fears about the baby [13][14]. Birth pain, which has become the main subject in pregnancy education, is one of the most powerful and di cult to control acute pain types.…”
Section: Introductionmentioning
confidence: 99%
“…Medical, institutional, legal, psychological, and sociodemographic factors, as well as the mother's desire, are among the main reasons for the increase in caesarean section rates (Akın et al, 2021; Korkut & Kaya, 2019). Fear of childbirth and self‐efficacy are reported to be reasons why women want caesarean sections (Arslantas et al, 2020; Long et al, 2018; Reyes & Rosenberg, 2019). While birth self‐efficacy refers to the woman's confidence in her own abilities, fear of childbirth refers to the fear that occurs at any stage of the perinatal period (Lowe, 2000; Wigert et al, 2020).…”
Section: Introductionmentioning
confidence: 99%